Pengaruh Citra Merek, Harga dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan PT. Graha Interior Surfacing - Michael Tanadi; Dennis Wijaya; Kriswan; Sari, Roza Maya; Efry Kurnia (Forum Kerjasama Pendidikan Tinggi, 2023)
This study aims to determine the effect of brand image, price, and service quality on customer satisfaction at PT Graha Interior Surfacing. This study uses quantitative data types and a research sample of 100 samples calculated using the Lemeshow formula. The results of the study partially show that brand image influences customer satisfaction at PT Graha Interior Surfacing, price influences customer satisfaction at PT Graha Interior Surfacing and service quality influences customer satisfaction at PT Graha Interior Surfacing. Simultaneously, brand image, price, and service quality affect PT Graha Interior Surfacing customer satisfaction.